Herpes Simplex Virus, Alzheimer’s Disease and a Possible Role for Rab GTPases - Bearer, Elaine L.; Wu, Chengbiao (Frontiers in Cell and Developmental Biology, 2019)
Herpes simplex virus (HSV) is a common pathogen, infecting 85% of adults in the United States. After reaching the nucleus of the long-lived neuron, HSV may enter latency to persist throughout the life span. Re-activation of latent herpesviruses is associated with progressive cognitive impairment and Alzheimer’s disease (AD). As an enveloped DNA virus, HSV exploits cellular membrane systems for its life cycle, and thereby comes in contact with the Rab family of GTPases, master regulators of intracellular membrane dynamics. Knock-down and overexpression of specific Rabs reduce HSV production. Disheveled membrane compartments could lead to AD because membrane sorting and trafficking are crucial for synaptic vesicle formation, neuronal survival signaling and Abeta production. Amyloid precursor protein (APP), a transmembrane glycoprotein, is the parent of Abeta, the major component of senile plaques in AD. Up-regulation of APP expression due to HSV is significant since excess APP interferes with Rab5 endocytic trafficking in neurons. Here, we show that purified PC12-cell endosomes transport both anterograde and retrograde when injected into the squid giant axon at rates similar to isolated HSV. Intracellular HSV co-fractionates with these endosomes, contains APP, Rab5 and TrkA, and displays a second membrane. HSV infected PC12 cells up-regulate APP expression. Whether interference with Rabs has a specific effect on HSV or indirectly affects membrane compartment dynamics co-opted by virus needs further study. Ultimately Rabs, their effectors or their membrane-binding partners may serve as handles to reduce the impact of viral re-activation on cognitive function, or even as more general-purpose anti-microbial therapies.